Inferior Vena Cava agenesis presenting as deep vein thrombosis in an eight year-old girl. Issue 3 (10th April 2023) - Mentesidou, Lida; Dettoraki, Athina; Michalopoulou, Aikaterini; Pergantou, Helen; Malama, Astero; Gavra, Maria; Bachou, Theodora
Abstract : Agenesis of vena cava inferior (AVCI) is a rare congenital malformation with a prevalence of 0.0005–1% in the general population. High level of suspicion is required in young patients with deep vein thrombosis (DVT), particularly bilateral. We present an 8-year-old girl with AVCI presenting as bilateral lower extremity DVT and a review of the literature in pediatric cases with AVCI and DVT.